Circulating immune complexes and disease activity in Crohn's disease. Issue 7 (July 1978) - Fiasse, R; Lurhuma, A Z; Cambiaso, C L; Masson, P L; Dive, C
Abstract : Circulating immune complexes were determined in 59 consecutive patients with Crohn's disease and 100 blood donors by a double method based on the inhibition of the agglutinating activity of CIq and/or rheumatoid factor on the IgG-coated polystyrene particles. In patients, the incidence of positive immune complexes was 63% and 61% at first testing, 85% and 78% at subsequent determinations; there was a good correlation between the inhibition titres of CIq and those of rheumatoid factor (p less than 0.001). In blood donors, the incidence was 22% and 14% at low titre. The incidence of immune complexes was the lowest (36%) in the group of resected patients without signs of relapse; repeat determinations showed absence of immune complexes three months postoperatively. In patients medically treated for primary disease or relapse, rheumatoid factor titre higher than 1/1 was less frequent than in medically untreated patients with active disease (p less than 0.01). A significantly higher concentration of serum alpha-1-antitrypsin and orosomucoid, and a significantly lower level of serum iron were found in patients with an IC titre exceeding 1/1; longitudinal studies showed in most cases a concordance between the evolution of immune complex titres, inflammatory parameters and clinical status.